Digitalizacija na podeželju v Sloveniji: med razvojnimi koraki in digitalnimi razkoraki - Hauptman, Barbara (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2023)
Digitalization of rural areas is based on the establishment of digital infrastructure and the use of digital tools. In this process, there are significant differences between rural areas regarding development steps (e.g. time, investment, spatial aspect of establishing digital infrastructure and digital tools) and digital divides are constructed (differences in the availability and accessibility of digital infrastructure, use of digital tools), which were surveyed in area of the local action group (LAG) “Od Pohorja do Bohorja”, Slovenia. To gain insight into the pragmatic aspect of the direct user of digital infrastructure and digital tools in rural areas, we conducted an online survey which pointed out that local residents mostly perceive digitalization positively as a tool in everyday tasks, that primary school students perceive digitalization positively, and they are also aware of the negative aspects. Spatial analysis of the existing digital infrastructure indicated that it is deficient in most municipalities of the LAG “Od Pohorja do Bohorja”, rare investments in digital infrastructure are often limited to the centres of municipalities. Since digitalization has become an integral and often a key part of contemporary life and work, with the critical self-reflection of the interviewees (6) in the surveyed area, we recognized that each individual has a different perception, understanding and degree of use of digital infrastructure and digital tools. Empirical-conceptual findings of the focus group indicate the ineffectiveness of state authorities in investing in digital equipment, insufficient information content in the primary school curriculum and the large role of digital infrastructure and digital tools at work and in leisure time.
Keywords: digitalizacija na podeželju; digitalization in rural areas; podeželje; rural areas; Slovenia; Slovenija